Augmented reality for minimally invasive spinal surgery - Avrumova, Fedan; Lebl, Darren R. (Frontiers in Surgery, 2023)
Background: Augmented Reality (AR) is an emerging technology that can overlay computer graphics on to the real world and enhance visual feedback from information systems. Within the past several decades, innovations related to AR have been integrated into our daily lives, however its application in medicine, specifically in minimally invasive spine surgery (MISS) may be most important to understand. AR navigation provides auditory and haptic feedback which can further enhance surgeons’ capabilities and improve safety. Purpose: The purpose of this article is to address previous and current applications of AR, AR in MISS, limitations of today’s technology and future areas of innovation. Methods: A literature review related to applications of AR technology in pervious and current generations. Results: AR systems have been implemented for treatments related to spinal surgeries in recent years and AR may be an alternative to current approaches such as, traditional navigation, robotically assisted navigation (RAN), fluoroscopic guidance and freehand. As AR is capable projecting patient anatomy directly on the surgical field, it can eliminate concern for surgeon attention shift from the surgical field to navigated remote screens, line -of- sight interruption, and cumulative radiation exposure as demand for MISS increases. Conclusion: AR is a novel technology that can improve spinal surgery and limitations will likely have a great impact on future technology.